Associations between long-term exposure to wildfire-related particulate matter and site-specific cancer mortality: a national study in Brazil, 2010–16. (July 2022) - Yu, Pei; Xu, Rongbin; Li, Shanshan; Yue, Xu; Chen, Gongbo; Ye, Tingting; Coêlho, Micheline; Saldiva, Paulo; Sim, Malcolm R; Abramson, Michael J; Guo, Yuming
Abstract: Background: With the increasing frequency and duration of wildfires over the past 10 years, the effects of wildfire on health need to be better understood. Long-term exposure to particulate matter less than 2·5 μm in diameter (PM2·5) has been linked to cancer mortality. However, the long-term effects of wildfire-related PM2·5 exposure on cancer mortality risk were unknown. The aim of this study was to assess the association between wildfire-related PM2·5 and cancer mortality in Brazil on the basis of nationwide death records for the period of 2010–16. Methods: Nationwide cancer death records for the period of January 1 to December 31, 2010–16 were collected and linked with municipal-level, wildfire-related and non-wildfire-related PM2·5 concentrations at a 2·0° latitude by 2·5° longitude resolution. We applied a difference-in-difference approach with quasi-Poisson regression for data analysis. Relative risks (RRs) and 95% CIs for the exposure on specific cancer sites were estimated, and attributable fractions and cancer deaths were also calculated. Findings: 1 332 526 cancer deaths in adults (ie, individuals aged 20 years or older) from 5565 Brazilian municipalities covering a population of 136 million adults were included. The annual wildfire-related PM2·5 concentration was 2·38 μg/m 3 and the non-wildfire-related PM2·5 was 8·20 μg/m 3 . The RR for mortality from all cancers was 1·02 (95% CI 1·01–1·03) per μg/m 3 increase of wildfire-related PM2·5 concentration, which was higher than other sources of PM2·5 (1·01 [1·00–1·01]; p=0·0029). Wildfire-related PM2·5 was associated with higher mortality from cancers of the nasopharynx (RR 1·10 [95% CI 1·04–1·16]; p=0·0015), oesophagus (1·05 [1·01–1·08]; p=0·012), stomach (1·03 [1·01–1·06]; p=0·017), colon and rectum (1·08 [1·05–1·11]; p<0·0001), larynx (1·06 [1·02–1·11]; p=0·0031), skin (1·06 [1·00–1·12]; p=0·033), breast (1·04 [1·01–1·06]; p=0·0074), prostate (1·03 [1·01–1·06]; p=0·019), and testis (1·10 [1·03–1·17]; p=0·0022). For all-cancers combined, the attributable deaths were 37 per 100 000 people during the study period. Interpretation: Long-term exposure to wildfire-related PM2·5 can increase the risk of cancer mortality at various sites. The effect was greater for wildfire-related PM2·5 than for PM2·5 from other sources. Funding: Australian Research Council and National Health & Medical Research Council; China Scholarship Council.